H3 K27M-Altered Diffuse Midline Gliomas: A Review - Karol Wiśniewski; Andrew Ghaly; Kate Drummond; Andreas Fahlstrӧm (Indian Journal of Neurosurgery, 2023)
Diffuse midline glioma H3 K27M-altered is a recently renamed high-grade glioma in the 2021 World Health Organization (WHO) Classification of Central Nervous System Tumors, previously being labelled diffuse midline glioma H3 K27M-mutant in the 2016 update and diffuse intrinsic pontine glioma prior to 2016. After identification of multiple alterations causing H3 K27 hypomethylation, the definition of this tumor subtype was changed. To further characterize this new entity in both the pediatric and adult population, we conducted a review of the current literature, investigating genetic, epidemiological, clinical, radiological, histopathological, treatment and prognostic characteristics, particularly highlighting the differences between adults and children. This tumor is more common in children, and has a poorer prognosis. Additionally, childhood H3 K27-altered gliomas are more common in the brainstem, but more common in the thalamus in adults. Sadly, limited treatment options exist for these tumors, with radiotherapy the only treatment shown to improve overall survival.